DESAIN SISTEM INSTALASI ENERGI LISTRIK MENGGUNAKAN TENAGA SURYA PADA GEDUNG LABORATORIUM FISIKA – UNIMED - Hutur P Siahaan; Eka Dodi Suryanto; Dian Putra Saragi (JURNAL ILMIAH PENELITIAN MAHASISWA, 2026)
This research aims to design and analyze a hybrid solar power plant (PLTS)-based electrical energy installation system in the Physics Laboratory Building of Medan State University (UNIMED) as a sustainable energy solution. The methods used include electrical load analysis, solar energy potential evaluation, and system simulation to determine the optimal configuration technically and economically. The results show that the daily electrical energy demand of ±99 kWh/day can be met by a 17.4 kWp solar power plant system capable of supplying approximately 60% of the energy requirement, supported by a 37.1 kWh battery and a 21 kW inverter, while the remainder is met by the PLN grid. This hybrid system has been proven to improve energy supply reliability, reduce dependence on conventional energy, and has the potential to provide long-term cost efficiency, making it suitable for implementation as part of renewable energy development in the campus environment.